ABREVIASI PADA RUBRIK HUMANIORA KOMPAS.ID EDISI NOVEMBER 2022-2023 - Vivi Antika Zahra Juliawanti; Dian Hartati; Hendra Setiawan (Universitas Negeri Makassar, 2025)
This research aims to describe the types of abbreviations in the Humaniora rubric of Kompas.id. This type of research is qualitative research and descriptive method. The data source in the research is the Humanities section of Kompas.id November 2022-2023 edition with a total of 58 news articles. Data were collected through observation, documentation, listening, and note taking. Data analysis in the research used data reduction, data presentation, and conclusion or verification. Based on the results of the research, six abbreviation processes, three acronym processes, four contraction processes, four fragmentation processes, and three letter symbol processes were found. Abbreviation is the most dominant form used in Kompas.id online media writing.